2012
DOI: 10.1016/j.compgeo.2011.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of centrifuge tests on homogeneous and heterogeneous soil models

Abstract: a b s t r a c tSoil liquefaction is a major cause of seismic damage in cohessionless soil during earthquakes. From past numerical and experimental research it has been observed that more excess pore water pressure (EPWP) is generated during earthquakes in a heterogeneous soil deposit than in the corresponding homogeneous soil with relative density equal to the average relative density of the heterogeneous soil. This interesting phenomenon is investigated here, by numerically simulating centrifuge experiments o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The earthquake energy also can be expressed in terms of Arias Intensity (AI) [5]. This AI can be represented as damage potential of an earthquake [16].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The earthquake energy also can be expressed in terms of Arias Intensity (AI) [5]. This AI can be represented as damage potential of an earthquake [16].…”
Section: Resultsmentioning
confidence: 99%
“…It can also be observed from these figures that the amplification is higher in homogenous soil model as compared to that in heterogeneous soil. One most important reason behind this is that the EPWP generation is more in heterogeneous soil than that in homogenous soil which causes more softening of heterogeneous soil layers [5].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, the vertical loading is 500 N, the frequency of excitation is 16 Hz, the dimensionless width of the rigid foundation is W 0.2, the dimensionless depth for the topsoil layer is H T 1, and the dimensionless depth for the subsoil layer is H S 5. In addition, the dimensionless distance for calculation points on the ground surface is from 0.1 to 4 away from the vibration source, with an interval of 0.05. e detailed calculation parameters of soil and Duxseal which refer to the works of Pak et al [8] and Chakrabortty and Popescu [10] are listed in Table 1.…”
Section: Vibration Isolation For Duxsealmentioning
confidence: 99%
“…Laboratory tests in heterogeneous soils have shown that the ∆p w is generated first in loose deposits and when water migrates to neighboring dense sand, it is softened and eventually liquefied. This interaction also affects the liquefactioninduced settlements (Coelho et al 2004, Dashti et al 2010, Chakrabortty and Popescu 2012. Extensive research has been performed on the calculation of these settlements but rarely they include the variability of soil properties and modeling of different soil deposits (Koutsourelakis et al 2002, among others).…”
Section: Introductionmentioning
confidence: 99%